O autor contemporâneo e a máquina produtora de mitos - Martinelli Filho, Nelson (2016)
Amidst the range of research and work that has been produced in the last decades in Brazil on topics such as author's return, written himself and autofiction, it often has been said about the emergence of an “myth of the author” (or “writer myth”) – and such expressions indiscriminately have appeared in a variety of different texts of different researchers. However, in most cases where these terms are referred little theoretical distinction is made, frequently taking them widely in a dictionary and generic sense most of the times. So, taking as a starting point, the expression myth of the author, this thesis intends to investigate how, considering the heated discussions on the author's figure during the twentieth century and the literary productions of the contemporary, this mythical image has been systematized (especially as a vestige of contemporary mythical behavior), to which or to whom the image has served, what are its purposes and its consequences. Thus, a deepening in relation to a) author notions, from names like Roland Barthes, Michel Foucault, Giorgio Agamben and Roger Chartier; and b) myth, retaking some key concepts such as Mircea Eliade, Paul Veyne and Jean-Pierre Vernant, until you reach the Barthes of Mythologies, which provides a basis for discussions within the contemporary literature. These issues are related to novels by Chico Buarque – Estorvo (1991), Benjamim (1995), Budapeste (2003), Leite derramado (2009) and O irmão alemão (2014) – in search of a detailed analysis of the relationship between the persona who writes the editorial and marketing system, in order to keep up with the author of the myth-building strategies.